Answer:
(a) First order linear separable differential equation
(b)
![y(x)=2+C_1e^(x-x^2) \\\\I=(-\infty,\infty)](https://img.qammunity.org/2021/formulas/mathematics/college/dk5u2r2uzvj1rtf5mtodwnoj0dct24jn4q.png)
(c)
(d)
![y(x)=2-e^(x-x^2)](https://img.qammunity.org/2021/formulas/mathematics/college/ifdjxx4jgwm8m4952j3x16gvlqbm71qpp7.png)
Explanation:
(b) Solve for
![(dy)/(dx)](https://img.qammunity.org/2021/formulas/mathematics/high-school/uixpzcj18ltl0o4d3t4rqypg7shavk8rb9.png)
![(dy)/(dx)=4x+y-2xy-2\\ \\Simplify\\\\(dy)/(dx)=(2x-1)(2-y)\\\\Divide\hspace{3}both\hspace{3}sides\hspace{3}by\hspace{3}2-y\hspace{3}and\hspace{3}multiply\hspace{3}both\hspace{3}sides\hspace{3}by\hspace{3}dx\\\\(dy)/(2-y)=(2x-1) dx\\\\Integrate\hspace{3}both\hspace{3}sides\\\\\int(dy)/(2-y) \, =\int\ (2x-1) dx\\\\Evaluate\hspace{3}the\hspace{3}integrals\\\\-log(2-y)=x^2-x+C_1\\\\Solving\hspace{3}for\hspace{3}y\\\\y=2+C_1e^(x-x^2)](https://img.qammunity.org/2021/formulas/mathematics/college/ccq6hy1gz1gi2a868qd62p07el2qi8r2v5.png)
The domain of y is:
![x\in R\hspace{3}or\hspace{3}(-\infty,\infty)](https://img.qammunity.org/2021/formulas/mathematics/college/gu6djwve3zcz96btioveukkfcpefzymvf7.png)
So the lasrgest interval I on which the solution is defined is:
![I=(-\infty,\infty)](https://img.qammunity.org/2021/formulas/mathematics/college/so1ems9xejv4prtvqtwqz3t9kqab4o1a9p.png)
(c)
Differentiate y:
![(dy)/(dx)=C_1(1-2x)e^(x-x^2) =C_1e^(x-x^2)-2xC_1e^(x-x^2)](https://img.qammunity.org/2021/formulas/mathematics/college/jxwyzlahjgjzcufyhhsfsctlt0pr0un9qq.png)
Evaluate this result into the differential equation:
![(dy)/(dx)=4x+y-2xy-2\\\\C_1e^(x-x^2) -2xC_1e^(x-x^2) =4x+2+C_1e^(x-x^2)-4x-2xC_1e^(x-x^2)-2\\\\C_1e^(x-x^2) -2xC_1e^(x-x^2) =C_1e^(x-x^2) -2xC_1e^(x-x^2)](https://img.qammunity.org/2021/formulas/mathematics/college/qdh82qlgw3ob8t6ye1t22unmnix3xwk0h7.png)
Therefore, the solution is correct.
(d)
Simply evaluate the function y for x=0 and solve for C1:
![y(0)=2+C_1e^(0-0^2) =1\\\\2+C_1e^0=1\\\\2+C_1*1=1\\\\2+C_1=1\\\\C_1=-1](https://img.qammunity.org/2021/formulas/mathematics/college/41wkd5ln8i17xikzlc9pv2yfioi7kas3fb.png)
Finally substitute into y:
![y(x)=2-e^(x-x^2)](https://img.qammunity.org/2021/formulas/mathematics/college/ifdjxx4jgwm8m4952j3x16gvlqbm71qpp7.png)